Experimental drought reduces the transfer of recently fixed plant carbon to soil microbes and alters the bacterial community composition in a mountain meadow. Issue 3 (31st October 2013) - Fuchslueger, Lucia; Bahn, Michael; Fritz, Karina; Hasibeder, Roland; Richter, Andreas
Summary Drought affects plants and soil microorganisms, but it is still not clear how it alters the carbon (C) transfer at the plant–microbial interface. Here, we tested direct and indirect effects of drought on soil microbes and microbial turnover of recent plant‐derived C in a mountain meadow. Microbial community composition was assessed using phospholipid fatty acids (PLFAs); the allocation of recent plant‐derived C to microbial groups was analysed by pulse‐labelling of canopy sections with 13CO2 and the subsequent tracing of the label into microbial PLFAs. Microbial biomass was significantly higher in plots exposed to a severe experimental drought. In addition, drought induced a shift of the microbial community composition, mainly driven by an increase of Gram‐positive bacteria. Drought reduced belowground C allocation, but not the transfer of recently plant‐assimilated C to fungi, and in particular reduced tracer uptake by bacteria. This was accompanied by an increase of 13C in the extractable organic C pool during drought, which was even more pronounced after plots were mown. We conclude that drought weakened the link between plant and bacterial, but not fungal, C turnover, and facilitated the growth of potentially slow‐growing, drought‐adapted soil microbes, such as Gram‐positive bacteria.